Đẩy nhanh tiến trình chuyển đổi số hoạt động thông tin-thư viện để trở thành thư viện số thông minh tại Học viện Chính trị Quốc gia Hồ Chí Minh - Nguyễn, Thị Tuyết Vân (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article analyzes the impact of digital transformation on information - library activities. Studying the current situation of digital transformation of information - library activities of Ho Chi Minh National Academy of Politics today and proposing solutions to promote digital transformation of information - library activities of Ho Chi Minh National Academy of Politics in the near future.